Has COVID-19 pushed us to the brink of a triple crisis? insights from the wellness-resilience prioritization matrix / Shirly Wong Siew Ling ... [et al.] - Wong Siew Ling, Shirly; Ang Jing Ying, Mandy; Keng Sheng, Chew; Lau, Evan (2022)
The COVID-19 pandemic has badly wounded many areas of people’s lives, distressed the lives of families with millions of deaths, harmed the labor market with overwhelming consequences of massive layoff, on top of the loneliness extended from social isolation. All these have evidently marked effect on people’s mental health. Therefore, mental health crisis is believed to be another health-related catastrophe hiding in plain sight. In view of this, Wellness-Resilience Prioritization Matrix (WRPM) has been developed to provide a much-needed understanding of the linkage between mental health and mental illness condition under the presence of household effects for better priority setting for mental health interventions. WRPM is an improved version of the traditional illness-wellness continuum model reckoned by Keyes (2002). The original two-dimensional illness-wellness interaction framework is innovated into a four-dimensional model to account for household dynamics, such as family structure and household income. The attractiveness of this model rests with its simplicity in summarizing the two correlated but differentiated latent elements into a graphic interpretation of illness-wellness relationship with additional insights from the household effects. All findings discovered from WRPM ultimately directed into a similar conclusion, that is the impact of COVID-19 towards mental health is indeed sizeable as individual, regardless they are living under single or coupled household structure are equally painful mentally during the hard time of pandemic crisis. WRPM is useful to inform policymakers and health practitioners on how to enrich available programs and initiatives to promote mental health and well-being in the community. Besides, WRPM helps the Wellness and Mental Health Service Providers to design an alternative form of professional care appropriate for individual’s social and cultural values which can be established according to the illness-wellness situation.